Heparan sulfate is the attachment factor associated with channel catfish virus infection on host cells - Yu, Fei; Chen, Hongxun; Xu, Jiehua; Wang, Yu; Nie, Chunlan; Song, Siyang; Meng, Lihui; Hao, Kai; Zhao, Zhe (Frontiers in Veterinary Science, 2023)
Channel catfish virus (CCV; family Alloherpesviridae) infects channel catfish, causing great harm to aquaculture fisheries and economic development. Attachment is the first step in viral infection and relies on the interaction of virions with components of the extracellular matrix (ECM). The present study aimed to explored the role of the main three ECM components in CCV attachment. Western blotting and quantitative real-time PCR analysis showed that neither collagen nor hyaluronic acid treatments had significant effects on CCV attachment. When exogenous heparin was used as a competitive inhibitor, the adhesion of heparin sodium salt to CCV was dose-dependent. When the concentration of heparin sodium salt was 10 mg/mL, the inhibitory effect on CCV infection of channel catfish ovary (CCO/BB) cells was more than 90%. Heparinase I could significantly prevent CCV attachment by digesting heparan sulfate on the cell surface, and both heparin sodium salt and heparinase I could dose-dependently reduce CCV titers, suggesting that heparin plays an important role in CCV attachment. In addition, the binding experiments between heparin-agarose beads and virions showed that CCV virions could specifically bind to heparin in a dose-dependent manner. The above results suggested that heparan sulfate might be an attachment factor involved in CCV infection of CCO/BB cells. These results increase our understand of the attachment mechanism of CCV and lay the foundation for further research on antiviral drugs.